Heterosis and combining ability studies in sesame (Sesamum indicum L.): HETEROSIS AND COMBINING ABILITY STUDIES IN SESAME - S R KUMHAR; SUSHILA SIROHI; BABITA KUMARI (Journal of Oilseeds Research, 2020)
Heterosis and combining ability analysis were carried out with three lines and nine testers during kharif 2018. The mean sum of squares due to parents showed significant differences for most of the characters, except oil content indicating the presence of sufficient variability among the parents. The mean squares due to hybrids were significant for almost all the characters studied. The estimation of gca variances were lower than sca variances which indicated the predominance of non-additive gene action for plant height, days to 50% flowering, days to maturity, number of effective branches/plant, number of capsules/ plant, number of seeds/capsule, harvest index, seed yield/plant, capsule bearing length and additive gene action for oil content. Non-additive genetic variances may be utilized to increase the yield levels by heterosis breeding. The parents, TKG-22, GT-10 and RT-372 were good general combiners for seed yield and contributing characters. The best specific crosses, RT-351 × TKG-22, RT-54 × TKG-22 and RT-54 × RT-372 were most heterotic hybrids for seed yield and found promising for yield contributing characters. These crosses involved average × average, average × poor, average × good parents.